Generally applicable breakage functions derived from single particle comminution data - Meier, Matthias; John, Edgar; Wieckhusen, Dierk; Wirth, Wolfgang; Peukert, Wolfgang (Powder Technology, 2009)
Nine different substances with widely varying properties have been impacted on a rigid target at different velocities. The obtained fragment size distributions have been analyzed in order to obtain a mathematical expression for the breakage functions. The breakage function was modeled as a bimodal logarithmic normal distribution. It was found that the parameters of these approximated breakage functions change with impact energy in the same way for all substances. It could be shown that the breakage function is both size and material dependent. The material dependency can be expressed via the dimensionless stressing parameter f* (Mat) . x . (W* (m.kin) - W* (m.min)), where f* (Mat) and x . W* (m.min) are breakage parameters that can be determined from single particle comminution experiments or estimated from other mechanical properties (namely the brittleness index of the material). No difference in the breakage functions was found for impacts under 60 degrees and 90 degrees. The results of this work allow the prediction of breakage functions for impacting particles. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Comminution; Grinding; Breakage function; Single particle experiments; Material properties